Rotorcraft applications of active gurney flap investigated within the clean-sky project COMROTAG - Stalewski, W. (My University, 2015)
Computational investigations within the EU 7th FWP Project COMROTAG have been carried out. The main goal of the Project is to develop, implement and validate through computational tests the methodology of simulation of the flow around helicopter rotors with blades equipped with the Active Gurney Flaps (AGF). The AGF is a small, flat tab located at lower surface of the blade, near its trailing edge. The tab is cyclically deployed and retracted perpendicularly to the blade surface. When deployed, the tab deflects air stream behind the blade trailing edge downwards, leading to the lift increase, which is especially important on the retreating blade of the rotor. On the advancing blade, the tab is retracted to minimise rotor torque. The AGF may be potentially used for the active control of flow on helicopter-rotor blades. The paper presents results of already finished stages of the COMROTAG project. The initial stage was focused on development of innovative methodology of computational simulation of flight of the helicopter main rotor with blades equipped with AGF. In general, the methodology is based on solution of the Navier-Stokes Equations via Finite Volume Method. The motion of helicopter rotor blades equipped with dynamically deployed AGF is modelled using Deforming Mesh and Sliding Mesh techniques. First stage of validation of the developed methodology concerned quasi-2D investigations of rotor-blade segment equipped with the AGF. The computational results have been compared with experimental data obtained in wind-tunnel tests.
Keywords: Aerodynamics